Global health competencies according to nursing faculty from Brazilian higher education institutions (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to identify the agreement of faculty affiliated with Brazilian higher education institutions about the global health competencies needed for undergraduate nursing students' education and whether these competencies were covered in the curriculum offered at the institution where they were teaching. METHOD: exploratory-descriptive study, involving 222 faculty members who answered the Brazilian version of the "Questionnaire on Core Competencies in Global Health", made available electronically on the website Survey Monkey. RESULTS: participants predominantly held a Ph.D. (75.8%), were women (91.9%) and were between 40 and 59 years of age (69.3%). The mean and standard deviation of all competencies questioned ranged between 3.04 (0.61) and 3.88 (0.32), with scores for each competency ranging from 1 "strongly disagree" to 4 "strongly agree". The results demonstrated the respondents' satisfactory level of agreement with the global health competencies. CONCLUSIONS: the study demonstrated a high mean agreement level of the nursing faculty from Brazilian HEI with the global health competencies in the questionnaire. The curricula of the HEI where they teach partially address some of these. The competencies in the domain "Globalization of health and health care" are the least addressed.